A TPA high elastic material composition and preparation method thereof

By using TPE elastomer, EPDM, EVA and other matrix materials in TPA materials, and adding modified nano-concave and convex rods and adjuster-resistant functional additives, the problem of insufficient performance of existing TPA materials is solved, and higher anti-slip, breathability and weather resistance are achieved.

CN119463268BActive Publication Date: 2025-04-22QUANZHOU BAOFENG SHOES CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510066902.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-22
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

The elastic properties of existing TPA materials are average, with poor cold and hot and ultraviolet weather resistance, low stability, insufficient anti-slip and breathability, which limits the efficiency of the product.

Method used

TPE elastomer, EPDM, and EVA are used as substrates, zinc stearate, diapropyl peroxide, foaming agent, anti-aging agent and stearic acid are added as functional additives, and TPA high elastic material composition is prepared by mixing and combining modified nano-concave rods and adjusting agent resistance.

Benefits of technology

It significantly improves the anti-slip, breathability and elastic properties of TPA materials, while improving the product's hot and cold and ultraviolet weather resistance adaptability and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of TPA high elastic material, and specifically to a TPA high elastic material composition and a preparation method thereof, comprising the following steps: weighing raw materials according to weight: 35-45 parts of TPE elastomer, 10-15 parts of EPDM, 8-12 parts of EVA, 7-11 parts of modified nano-attapulgite, 6-9 parts of anti-adjustment, 4-6 parts of zinc stearate, 1-2 parts of diisopropylbenzene peroxide, 2-4 parts of foaming agent, 2-3 parts of antioxidant and 1-2 parts of stearic acid. The TPA high elastic material composition of the present invention adopts TPE elastomer, EPDM and EVA as a matrix, and by adding zinc stearate, diisopropylbenzene peroxide, foaming agent, antioxidant and stearic acid as functional additives, the anti-skid, air permeability and elastic properties of the obtained TPA high elastic material composition product are coordinated and improved, and the cold and hot, ultraviolet weathering adaptability of the product are remarkable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of TPA high elastic material, and in particular to a TPA high elastic material composition and a preparation method thereof. Background Art

[0002] TPA material is made of TPE elastomer, EPDM (ethylene propylene diene monomer rubber) and EVA (ethylene vinyl acetate) materials through processing and molding technology. The existing TPA material has average elastic performance, poor adaptability to heat and cold, and UV weathering, low product stability, and poor anti-slip and air permeability, which further limits the product's efficiency. Summary of the invention

[0003] In view of the defects of the prior art, the purpose of the present invention is to provide a TPA high elastic material composition and a preparation method thereof to solve the problems raised in the above background technology.

[0004] The present invention solves the technical problem by adopting the following technical solution:

[0005] The present invention provides a method for preparing a TPA high elastic material composition, comprising the following steps:

[0006] Step 1: weigh the raw materials according to weight: 35-45 parts of TPE elastomer, 10-15 parts of EPDM, 8-12 parts of EVA, 7-11 parts of modified nano-attapulgite, 6-9 parts of anti-adjustment agent, 4-6 parts of zinc stearate, 1-2 parts of dicumyl peroxide, 2-4 parts of foaming agent, 2-3 parts of antioxidant and 1-2 parts of stearic acid;

[0007] Step 2: The modified nano-attapulgite, the adjustment resistance, zinc stearate, and stearic acid are uniformly blended, and then sent into a mixer together with TPE elastomer, EPDM, EVA, dicumyl peroxide, a foaming agent, and an antioxidant for mixing at a mixing temperature of 120° C., a mixing time of 5 min, and a mixing speed of 100 r / min to obtain a mixing product;

[0008] Step 3: The mixed product is sent to an open mixer for mixing for 10 minutes, and then pressed into a 3 mm thin sheet. Finally, the thin sheet is placed in a flat vulcanizer for mold foaming treatment. After the foaming is completed, a TPA high elastic material composition is obtained.

[0009] Preferably, the compression foaming treatment adopts compression foaming at a pressure of 10 MPa and a temperature of 175° C. for 300 seconds; the foaming agent is foaming agent AC; and the antioxidant is antioxidant MB.

[0010] Preferably, the preparation method of the modified nano attapulgite is:

[0011] S01: Add 3-5 parts of nano-carbon powder and 2-4 parts of cerium nitrate solution to 5-8 parts of 4% dopamine hydrochloride solution by weight, then add 1-3 parts of silane coupling agent KH550, stir evenly, and obtain nano-carbon liquid;

[0012] S02: pre-treating the nano-attapulgite by stirring in a sufficient amount of hydrogen peroxide solution, then washing with boiling water for 3 times, filtering and drying to obtain the pre-treated nano-attapulgite;

[0013] The pretreated nano-attapulgite is placed in a nano-carbon solution 3-5 times the total weight of the pretreated nano-attapulgite for ultrasonic treatment, with an ultrasonic power of 350-400W for 30 minutes, filtered and dried to obtain a nano-carbon-polyphonic nano-attapulgite agent;

[0014] S03: The nano-compounded nano-attapulgite agent and the titanium dioxide modified liquid are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, the mixture is filtered and dried to obtain the modified nano-attapulgite.

[0015] Preferably, the mass fraction of the hydrogen peroxide solution is 2-5%; the mass fraction of the cerium nitrate solution is 3-6%.

[0016] Preferably, in S02, the stirring speed of the stirring pretreatment is 150-200 r / min, and the stirring is for 1 hour; in S03, the ball milling speed of the mixing ball milling treatment is 1000-1500 r / min, and the ball milling is for 2 hours.

[0017] Preferably, the preparation method of the titanium dioxide modified liquid is:

[0018] S031: 2-5 parts of titanium dioxide, 1-2 parts of sodium carboxymethyl cellulose and 5-8 parts of 5% chitosan solution are uniformly mixed by weight to obtain titanium dioxide solution;

[0019] S032: First, the nano-silicon dioxide is stirred thoroughly in a 5% by mass sulfuric acid solution, and then washed with water, filtered, and dried to obtain dry nano-silicon dioxide; the dry nano-silicon dioxide, boron nitride and a 3-5% by mass lanthanum chloride solution are mixed and ball-milled in a weight ratio of (3-5):2:(5-7), the ball milling speed is 1000r / min, the ball milling is carried out for 2h, and after the ball milling is completed, the mixture is filtered, dried, and the added modifier is obtained;

[0020] S033: adding the additive modifier to the titanium dioxide solution whose total weight is 3-5 times of the additive modifier, and stirring the solution. After the stirring is completed, a titanium dioxide modified solution is obtained.

[0021] Preferably, in S033, the stirring temperature of the stirring treatment is 60-65° C., the stirring speed is 550-750 r / min, and the stirring is performed for 20 min.

[0022] Preferably, the preparation method of the adjustment-resistant material is:

[0023] S101: silane coupling agent KH560, ethanol and water are mixed in a weight ratio of 3:5:1 to obtain a silane coupling liquid; then barium carbonate is added to a sufficient amount of the silane coupling liquid and stirred to obtain a barium carbonate liquid;

[0024] S102: 5-8 parts of barium carbonate solution, 1-2 parts of nano-silica sol, 3-4 parts of sodium silicate solution and 2-3 parts of magnesium oxide are mixed and ball-milled by weight at a ball-milling speed of 1500 r / min for 1 hour. After the ball-milling is completed, the mixture is filtered and dried to obtain an agent-resistant mixture.

[0025] Preferably, the mass fraction of the sodium silicate solution is 2-5%.

[0026] The present invention also provides a TPA high-elastic material composition, which is prepared by the preparation method of the TPA high-elastic material composition.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] 1. The TPA high elastic material composition of the present invention uses TPE elastomer, EPDM, and EVA as a matrix, and adds zinc stearate, dicumyl peroxide, a foaming agent, an antioxidant, and stearic acid as functional additives, and at the same time adds modified nano-attapulgite and an anti-adjustment agent to coordinate and coordinate the two, thereby obtaining a TPA high elastic material composition product with improved anti-slip, air permeability, and elastic properties, and at the same time, the product has significant effects on cold and hot, and UV weatherability adaptability;

[0029] 2. Modified nano-attapulgite: The nano-attapulgite is first stirred in a sufficient amount of hydrogen peroxide solution for pretreatment to optimize the dispersion and activity of the nano-attapulgite. At the same time, nano-carbon liquid is improved by ultrasonic treatment. The nano-carbon liquid uses nano-carbon as a matrix and optimizes the air permeability of the system through the porous structure of nano-carbon. At the same time, the nano-attapulgite has a sheet spacing to improve the air permeability of the system. At the same time, nano-carbon powder, cerium nitrate solution, 4% hydrochloric acid dopamine solution by mass and silane coupling agent KH550 are blended. The nano-attapulgite is optimized and improved through the coordination of the raw materials, thereby enhancing the product. Performance effect: the improved nano-compounded nano-attapulgite agent and titanium dioxide modified liquid are further coordinated and optimized. The titanium dioxide modified liquid is made of titanium dioxide powder, sodium carboxymethyl cellulose and chitosan solution with a mass fraction of 5%. The raw materials are coordinated and matched, and the nano-silicon dioxide is treated with sulfuric acid solution to optimize its activity efficiency. At the same time, it is coordinated and matched with boron nitride and lanthanum chloride solution to further improve the titanium dioxide solution. Therefore, the nano-compounded nano-attapulgite agent and titanium dioxide modified liquid are further adjusted and improved, so that the performance of the product is coordinated and improved, and the performance stability effect is obvious.

[0030] 3. The anti-adjustment agent is treated with barium carbonate in silane coupling liquid to optimize the interface of barium carbonate. At the same time, it is mixed with nano-silica sol, sodium silicate solution and magnesium oxide for ball milling. Through the mutual coordination between the raw materials, the reinforcement effect of the prepared anti-adjustment agent and modified nano-attapulgite is further enhanced, thereby further improving the performance of the product. DETAILED DESCRIPTION

[0031] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] A method for preparing a TPA high elastic material composition of this embodiment comprises the following steps:

[0033] Step 1: weigh the raw materials according to weight: 35-45 parts of TPE elastomer, 10-15 parts of EPDM, 8-12 parts of EVA, 7-11 parts of modified nano-attapulgite, 6-9 parts of anti-adjustment agent, 4-6 parts of zinc stearate, 1-2 parts of dicumyl peroxide, 2-4 parts of foaming agent, 2-3 parts of antioxidant and 1-2 parts of stearic acid;

[0034] Step 2: The modified nano-attapulgite, the adjustment resistance, zinc stearate, and stearic acid are uniformly blended, and then sent into a mixer together with TPE elastomer, EPDM, EVA, dicumyl peroxide, a foaming agent, and an antioxidant for mixing at a mixing temperature of 120° C., a mixing time of 5 min, and a mixing speed of 100 r / min to obtain a mixing product;

[0035] Step 3: The mixed product is sent to an open mixer for mixing for 10 minutes, and then pressed into a 3 mm thin sheet. Finally, the thin sheet is placed in a flat vulcanizer for mold foaming treatment. After the foaming is completed, a TPA high elastic material composition is obtained.

[0036] The compression foaming process of this embodiment adopts compression foaming at a pressure of 10 MPa and a temperature of 175° C. for 300 seconds; the foaming agent is foaming agent AC; and the antioxidant is antioxidant MB.

[0037] The preparation method of the modified nano attapulgite of this embodiment is:

[0038] S01: Add 3-5 parts of nano-carbon powder and 2-4 parts of cerium nitrate solution to 5-8 parts of 4% dopamine hydrochloride solution by weight, then add 1-3 parts of silane coupling agent KH550, stir evenly, and obtain nano-carbon liquid;

[0039] S02: pre-treating the nano-attapulgite by stirring in a sufficient amount of hydrogen peroxide solution, then washing with boiling water for 3 times, filtering and drying to obtain the pre-treated nano-attapulgite;

[0040] The pretreated nano-attapulgite is placed in a nano-carbon solution 3-5 times the total weight of the pretreated nano-attapulgite for ultrasonic treatment, with an ultrasonic power of 350-400W for 30 minutes, filtered and dried to obtain a nano-carbon-polyphonic nano-attapulgite agent;

[0041] S03: The nano-compounded nano-attapulgite agent and the titanium dioxide modified liquid are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, the mixture is filtered and dried to obtain the modified nano-attapulgite.

[0042] The mass fraction of the hydrogen peroxide solution in this embodiment is 2-5%; the mass fraction of the cerium nitrate solution is 3-6%.

[0043] In S02 of this embodiment, the stirring speed of the stirring pretreatment is 150-200 r / min, and the stirring is for 1 hour; in S03, the ball milling speed of the mixing ball milling treatment is 1000-1500 r / min, and the ball milling is for 2 hours.

[0044] The preparation method of the titanium dioxide modified liquid of this embodiment is:

[0045] S031: 2-5 parts of titanium dioxide, 1-2 parts of sodium carboxymethyl cellulose and 5-8 parts of 5% chitosan solution are uniformly mixed by weight to obtain titanium dioxide solution;

[0046] S032: First, the nano-silicon dioxide is stirred thoroughly in a 5% by mass sulfuric acid solution, and then washed with water, filtered, and dried to obtain dry nano-silicon dioxide; the dry nano-silicon dioxide, boron nitride and a 3-5% by mass lanthanum chloride solution are mixed and ball-milled in a weight ratio of (3-5):2:(5-7), the ball milling speed is 1000r / min, the ball milling is carried out for 2h, and after the ball milling is completed, the mixture is filtered, dried, and the added modifier is obtained;

[0047] S033: adding the additive modifier to the titanium dioxide solution whose total weight is 3-5 times of the additive modifier, and stirring the solution. After the stirring is completed, a titanium dioxide modified solution is obtained.

[0048] In S033 of this embodiment, the stirring temperature of the stirring treatment is 60-65° C., the stirring speed is 550-750 r / min, and the stirring is performed for 20 minutes.

[0049] The preparation method of the resistant agent of this embodiment is:

[0050] S101: silane coupling agent KH560, ethanol and water are mixed in a weight ratio of 3:5:1 to obtain a silane coupling liquid; then barium carbonate is added to a sufficient amount of the silane coupling liquid and stirred to obtain a barium carbonate liquid;

[0051] S102: 5-8 parts of barium carbonate solution, 1-2 parts of nano-silica sol, 3-4 parts of sodium silicate solution and 2-3 parts of magnesium oxide are mixed and ball-milled by weight at a ball-milling speed of 1500 r / min for 1 hour. After the ball-milling is completed, the mixture is filtered and dried to obtain an agent-resistant mixture.

[0052] The mass fraction of the sodium silicate solution in this embodiment is 2-5%.

[0053] The TPA high-elastic material composition of this embodiment is prepared by the preparation method of the TPA high-elastic material composition.

[0054] Embodiment 1: A method for preparing a TPA high elastic material composition, comprising the following steps:

[0055] Step 1: weigh the raw materials according to weight: 35 parts of TPE elastomer, 10 parts of EPDM, 8 parts of EVA, 7 parts of modified nano-attapulgite, 6 parts of anti-adjustment agent, 4 parts of zinc stearate, 1 part of dicumyl peroxide, 2 parts of foaming agent, 2 parts of antioxidant and 1 part of stearic acid;

[0056] Step 2: The modified nano-attapulgite, the adjustment resistance, zinc stearate, and stearic acid are uniformly blended, and then sent into a mixer together with TPE elastomer, EPDM, EVA, dicumyl peroxide, a foaming agent, and an antioxidant for mixing at a mixing temperature of 120° C., a mixing time of 5 min, and a mixing speed of 100 r / min to obtain a mixing product;

[0057] Step 3: The mixed product is sent to an open mixer for mixing for 10 minutes, and then pressed into a 3 mm thin sheet. Finally, the thin sheet is placed in a flat vulcanizer for mold foaming treatment. After the foaming is completed, a TPA high elastic material composition is obtained.

[0058] The compression foaming process of this embodiment adopts compression foaming at a pressure of 10 MPa and a temperature of 175° C. for 300 seconds; the foaming agent is foaming agent AC; and the antioxidant is antioxidant MB.

[0059] The preparation method of the modified nano attapulgite of this embodiment is:

[0060] S01: Add 3 parts of nano-carbon powder and 2 parts of cerium nitrate solution to 5 parts of 4% dopamine hydrochloride solution by weight, then add 1 part of silane coupling agent KH550, stir evenly, and obtain nano-carbon liquid;

[0061] S02: pre-treating the nano-attapulgite by stirring in a sufficient amount of hydrogen peroxide solution, then washing with boiling water for 3 times, filtering and drying to obtain the pre-treated nano-attapulgite;

[0062] The pretreated nano-attapulgite was placed in a nano-carbon solution 3 times the total weight of the pretreated nano-attapulgite for ultrasonic treatment, with an ultrasonic power of 350 W for 30 minutes, and then filtered and dried to obtain a nano-carbon-polyphonic nano-attapulgite agent;

[0063] S03: The nano-compounded nano-attapulgite agent and the titanium dioxide modified liquid are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, the mixture is filtered and dried to obtain the modified nano-attapulgite.

[0064] The mass fraction of the hydrogen peroxide solution in this embodiment is 2%; the mass fraction of the cerium nitrate solution is 3%.

[0065] In S02 of this embodiment, the stirring speed of the stirring pretreatment is 150 r / min, and the stirring is for 1 hour; in S03, the ball milling speed of the mixing ball milling treatment is 1000 r / min, and the ball milling is for 2 hours.

[0066] The preparation method of the titanium dioxide modified liquid of this embodiment is:

[0067] S031: 2 parts of titanium dioxide, 1 part of sodium carboxymethyl cellulose and 5 parts of 5% chitosan solution are mixed uniformly by weight to obtain titanium dioxide solution;

[0068] S032: First, the nano-silicon dioxide is stirred in a 5% sulfuric acid solution, then washed with water, filtered and dried to obtain dry nano-silicon dioxide; the dry nano-silicon dioxide, boron nitride and 3% lanthanum chloride solution are mixed and ball-milled in a weight ratio of 3:2:5, the ball-milling speed is 1000r / min, the ball-milling is carried out for 2h, and after the ball-milling is completed, the mixture is filtered and dried to obtain the added modifier;

[0069] S033: adding the additive modifier to the titanium dioxide solution whose weight is three times of the total weight of the additive modifier, and stirring the solution. After the stirring is completed, a titanium dioxide modified solution is obtained.

[0070] In S033 of this embodiment, the stirring temperature of the stirring treatment is 60° C., the stirring speed is 550 r / min, and the stirring time is 20 min.

[0071] The preparation method of the resistant agent of this embodiment is:

[0072] S101: silane coupling agent KH560, ethanol and water are mixed in a weight ratio of 3:5:1 to obtain a silane coupling liquid; then barium carbonate is added to a sufficient amount of the silane coupling liquid and stirred to obtain a barium carbonate liquid;

[0073] S102: 5 parts of barium carbonate solution, 1 part of nano-silica sol, 3 parts of sodium silicate solution and 2 parts of magnesium oxide are mixed and ball-milled by weight at a ball-milling speed of 1500 r / min for 1 hour. After the ball-milling is completed, the mixture is filtered and dried to obtain an agent-resistant mixture.

[0074] The mass fraction of the sodium silicate solution in this embodiment is 2%.

[0075] The TPA high-elastic material composition of this embodiment is prepared by the preparation method of the TPA high-elastic material composition.

[0076] Embodiment 2: A method for preparing a TPA high elastic material composition, comprising the following steps:

[0077] Step 1: Weigh the raw materials according to weight: 45 parts of TPE elastomer, 15 parts of EPDM, 12 parts of EVA, 11 parts of modified nano-attapulgite, 9 parts of anti-adjustment agent, 6 parts of zinc stearate, 2 parts of dicumyl peroxide, 4 parts of foaming agent, 3 parts of antioxidant and 2 parts of stearic acid;

[0078] Step 2: The modified nano-attapulgite, the adjustment resistance, zinc stearate, and stearic acid are uniformly blended, and then sent into a mixer together with TPE elastomer, EPDM, EVA, dicumyl peroxide, a foaming agent, and an antioxidant for mixing at a mixing temperature of 120° C., a mixing time of 5 min, and a mixing speed of 100 r / min to obtain a mixing product;

[0079] Step 3: The mixed product is sent to an open mixer for mixing for 10 minutes, and then pressed into a 3 mm thin sheet. Finally, the thin sheet is placed in a flat vulcanizer for mold foaming treatment. After the foaming is completed, a TPA high elastic material composition is obtained.

[0080] The compression foaming process of this embodiment adopts compression foaming at a pressure of 10 MPa and a temperature of 175° C. for 300 seconds; the foaming agent is foaming agent AC; and the antioxidant is antioxidant MB.

[0081] The preparation method of the modified nano attapulgite of this embodiment is:

[0082] S01: Add 5 parts of nano-carbon powder and 4 parts of cerium nitrate solution to 8 parts of 4% dopamine hydrochloride solution by weight, then add 3 parts of silane coupling agent KH550, stir evenly, and obtain nano-carbon liquid;

[0083] S02: pre-treating the nano-attapulgite by stirring in a sufficient amount of hydrogen peroxide solution, then washing with boiling water for 3 times, filtering and drying to obtain the pre-treated nano-attapulgite;

[0084] The pretreated nano-attapulgite is placed in a nano-carbon solution with a weight 5 times the total weight of the pretreated nano-attapulgite for ultrasonic treatment at an ultrasonic power of 400 W for 30 minutes, filtered and dried to obtain a nano-carbon-polyphonic nano-attapulgite agent;

[0085] S03: The nano-compounded nano-attapulgite agent and the titanium dioxide modified liquid are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, the mixture is filtered and dried to obtain the modified nano-attapulgite.

[0086] The mass fraction of the hydrogen peroxide solution in this embodiment is 5%; the mass fraction of the cerium nitrate solution is 6%.

[0087] In S02 of this embodiment, the stirring speed of the stirring pretreatment is 200 r / min, and the stirring is for 1 hour; in S03, the ball milling speed of the mixing ball milling treatment is 1500 r / min, and the ball milling is for 2 hours.

[0088] The preparation method of the titanium dioxide modified liquid of this embodiment is:

[0089] S031: 5 parts of titanium dioxide, 2 parts of sodium carboxymethyl cellulose and 8 parts of 5% chitosan solution are mixed uniformly by weight to obtain a titanium dioxide solution;

[0090] S032: First, the nano-silicon dioxide is stirred in a 5% by mass sulfuric acid solution, and then washed with water, filtered and dried to obtain dry nano-silicon dioxide; the dry nano-silicon dioxide, boron nitride and 5% by mass lanthanum chloride solution are mixed and ball-milled in a weight ratio of 5:2:7, the ball milling speed is 1000r / min, the ball milling is carried out for 2h, and after the ball milling is completed, the mixture is filtered and dried to obtain an added modifier;

[0091] S033: adding the additive modifier to the titanium dioxide solution whose total weight is 3-5 times of the additive modifier, and stirring the solution. After the stirring is completed, a titanium dioxide modified solution is obtained.

[0092] In S033 of this embodiment, the stirring temperature of the stirring treatment is 65° C., the stirring speed is 750 r / min, and the stirring is performed for 20 minutes.

[0093] The preparation method of the resistant agent of this embodiment is:

[0094] S101: silane coupling agent KH560, ethanol and water are mixed in a weight ratio of 3:5:1 to obtain a silane coupling liquid; then barium carbonate is added to a sufficient amount of the silane coupling liquid and stirred to obtain a barium carbonate liquid;

[0095] S102: 8 parts of barium carbonate solution, 2 parts of nano-silica sol, 4 parts of sodium silicate solution and 3 parts of magnesium oxide are mixed and ball-milled by weight at a ball-milling speed of 1500 r / min for 1 hour. After the ball-milling is completed, the mixture is filtered and dried to obtain an agent-resistant mixture.

[0096] The mass fraction of the sodium silicate solution in this embodiment is 5%.

[0097] The TPA high-elastic material composition of this embodiment is prepared by the preparation method of the TPA high-elastic material composition.

[0098] Embodiment 3: A method for preparing a TPA high elastic material composition, comprising the following steps:

[0099] Step 1: Weigh the raw materials according to weight: 40 parts of TPE elastomer, 12.5 parts of EPDM, 10 parts of EVA, 9 parts of modified nano-attapulgite, 7.5 parts of anti-adjustment agent, 5 parts of zinc stearate, 1.5 parts of dicumyl peroxide, 3 parts of foaming agent, 2.5 parts of antioxidant and 1.5 parts of stearic acid;

[0100] Step 2: The modified nano-attapulgite, the adjustment resistance, zinc stearate, and stearic acid are uniformly blended, and then sent into a mixer together with TPE elastomer, EPDM, EVA, dicumyl peroxide, a foaming agent, and an antioxidant for mixing at a mixing temperature of 120° C., a mixing time of 5 min, and a mixing speed of 100 r / min to obtain a mixing product;

[0101] Step 3: The mixed product is sent to an open mixer for mixing for 10 minutes, and then pressed into a 3 mm thin sheet. Finally, the thin sheet is placed in a flat vulcanizer for mold foaming treatment. After the foaming is completed, a TPA high elastic material composition is obtained.

[0102] The compression foaming process of this embodiment adopts compression foaming at a pressure of 10 MPa and a temperature of 175° C. for 300 seconds; the foaming agent is foaming agent AC; and the antioxidant is antioxidant MB.

[0103] The preparation method of the modified nano attapulgite of this embodiment is:

[0104] S01: Add 4 parts of nano-carbon powder and 3 parts of cerium nitrate solution to 6.5 parts of 4% dopamine hydrochloride solution by weight, then add 2 parts of silane coupling agent KH550, stir evenly, and obtain nano-carbon liquid;

[0105] S02: pre-treating the nano-attapulgite by stirring in a sufficient amount of hydrogen peroxide solution, then washing with boiling water for 3 times, filtering and drying to obtain the pre-treated nano-attapulgite;

[0106] The pretreated nano-attapulgite was placed in a nano-carbon solution with a weight of 4 times the total weight of the pretreated nano-attapulgite for ultrasonic treatment at an ultrasonic power of 375 W for 30 min, and then filtered and dried to obtain a nano-carbon-polyphonic nano-attapulgite agent;

[0107] S03: The nano-compounded nano-attapulgite agent and the titanium dioxide modified liquid are mixed and ball-milled in a weight ratio of 5:3. After the ball-milling is completed, the mixture is filtered and dried to obtain the modified nano-attapulgite.

[0108] The mass fraction of the hydrogen peroxide solution in this embodiment is 3.5%; the mass fraction of the cerium nitrate solution is 4.5%.

[0109] In S02 of this embodiment, the stirring speed of the stirring pretreatment is 175 r / min, and the stirring is for 1 hour; in S03, the ball milling speed of the mixing ball milling treatment is 1250 r / min, and the ball milling is for 2 hours.

[0110] The preparation method of the titanium dioxide modified liquid of this embodiment is:

[0111] S031: 3.5 parts of titanium dioxide, 1.5 parts of sodium carboxymethyl cellulose and 6.5 parts of 5% chitosan solution are mixed uniformly by weight to obtain titanium dioxide solution;

[0112] S032: First, the nano-silicon dioxide is stirred in a 5% by mass sulfuric acid solution, and then washed with water, filtered and dried to obtain dry nano-silicon dioxide; the dry nano-silicon dioxide, boron nitride and 4% by mass lanthanum chloride solution are mixed and ball-milled in a weight ratio of 4:2:6, the ball milling speed is 1000r / min, the ball milling is carried out for 2h, and after the ball milling is completed, the mixture is filtered and dried to obtain an added modifier;

[0113] S033: adding the added modifier to the titanium dioxide solution of 4 times the total weight of the added modifier, stirring, and completing the stirring to obtain the titanium dioxide modified solution.

[0114] In S033 of this embodiment, the stirring temperature of the stirring treatment is 62.5° C., the stirring speed is 600 r / min, and the stirring time is 20 min.

[0115] The preparation method of the resistant agent of this embodiment is:

[0116] S101: silane coupling agent KH560, ethanol and water are mixed in a weight ratio of 3:5:1 to obtain a silane coupling liquid; then barium carbonate is added to a sufficient amount of the silane coupling liquid and stirred to obtain a barium carbonate liquid;

[0117] S102: 6.5 parts of barium carbonate solution, 1.5 parts of nano-silica sol, 3.5 parts of sodium silicate solution and 2.5 parts of magnesium oxide are mixed and ball-milled by weight at a ball-milling speed of 1500 r / min for 1 hour. After the ball-milling is completed, the mixture is filtered and dried to obtain an agent-resistant mixture.

[0118] The mass fraction of the sodium silicate solution in this embodiment is 3.5%.

[0119] The TPA high-elastic material composition of this embodiment is prepared by the preparation method of the TPA high-elastic material composition.

[0120] Comparative Example 1:

[0121] The difference from Example 3 is that no modified nano attapulgite is added.

[0122] Comparative Example 2:

[0123] The difference from Example 3 is that no nano-polyadjustable nano-attapulgite agent is added in the preparation of the modified nano-attapulgite.

[0124] Comparative Example 3:

[0125] The difference from Example 3 is that no nano-carbon liquid is added in the preparation of the nano-polyadjustable nano-attapulgite agent.

[0126] Comparative Example 4:

[0127] The difference from Example 3 is that no nano-carbon powder or cerium nitrate solution is added in the preparation of the nano-carbon liquid.

[0128] Comparative Example 5:

[0129] Different from Example 3, no silane coupling agent KH550 and dopamine hydrochloride solution were added in the preparation of the nano-carbon liquid.

[0130] Comparative Example 6:

[0131] The difference from Example 3 is that no titanium dioxide modifying liquid is added in the preparation of the modified nano attapulgite.

[0132] Comparative Example 7:

[0133] The difference from Example 3 is that no anti-adjustment agent is added.

[0134] Comparative Example 8:

[0135] The difference from Example 3 is that no barium carbonate solution is added to the resistance agent.

[0136] Comparative Example 9:

[0137] The difference from Example 3 is that no barium carbonate is added in the preparation of the barium carbonate solution.

[0138] Comparative Example 10:

[0139] The difference from Example 3 is that no sodium silicate solution and magnesium oxide are added to the anti-adjustment agent.

[0140] The products of Examples 1-3 and Comparative Examples 1-10 were tested for elasticity, anti-slip and air permeability under normal conditions, and also tested for cold and hot weathering and UV weathering stability (the products were placed at -5°C for 24 hours, then at 70°C for 12 hours, and then irradiated with UV light for 6 hours at 500 kwh / m 2 ), the performance test results are shown in Table 1.

[0141] Table 1 Product performance test results of Examples 1-3 and Comparative Examples 1-10:

[0142]

[0143] From Examples 1-3 and Comparative Examples 1-10, it can be concluded that the resilience, anti-slip value and oxygen filtration rate performance effects of Example 3 of the present invention are all significant, the elasticity, anti-slip and air permeability of the product can achieve coordinated improvements, and the product has significant stability effects in cold and hot and UV weathering tests;

[0144] It can be seen from Comparative Example 1, Comparative Example 7 and Example 3 that the product performance deteriorates significantly when neither the modified nano-attapulgite nor the anti-adjustment agent is added to the product. Only when the two are coordinated and work together, the performance effect of the product is most significant.

[0145] From Comparative Examples 1-6 and Example 3, it can be seen that the modified nano-attapulgite preparation did not add the nano-compounded nano-attapulgite agent, did not add the nano-carbon liquid, did not add the nano-carbon powder, the cerium nitrate solution, the silane coupling agent KH550, the dopamine hydrochloride solution, and the titanium dioxide modifying liquid in the preparation of the modified nano-attapulgite, and the performance of the product tended to deteriorate;

[0146] The nano-complex nano-attapulgite agent obtained by combining the nano-carbon liquid obtained by the specific method of the present invention with the pre-treated nano-attapulgite, and the modified nano-attapulgite prepared by combining the titanium dioxide modified liquid, have the most significant product performance effects;

[0147] It can be seen from Comparative Examples 8-10 and Example 3 that the performance of the products tends to deteriorate when barium carbonate solution is not added to the anti-adjustment agent, barium carbonate is not added in the preparation of the barium carbonate solution, and sodium silicate solution and magnesium oxide are not added to the anti-adjustment agent. Only the anti-adjustment agent prepared by the method of the present invention in combination with barium carbonate solution, sodium silicate solution and magnesium oxide has the most significant performance effect. Other methods are not as obvious as the effect of the present invention. The preparation of the anti-adjustment agent of the present invention is proprietary, and only the method of the present invention is used to prepare the best effect.

[0148] Based on the above tests, the present invention further explores the product performance through titanium dioxide modified liquid.

[0149] Experimental Example 1:

[0150] The only difference from Example 3 is that no modifier is added to the titanium dioxide modified liquid.

[0151] Experimental Example 2:

[0152] The only difference from Example 3 is that no dry nano-silica is added in the preparation of the added modifier.

[0153] Experimental Example 3:

[0154] The only difference from Example 3 is that no boron nitride is added in the preparation of the added modifier.

[0155] Experimental Example 4:

[0156] The only difference from Example 3 is that no lanthanum chloride solution is added during the preparation of the added modifier.

[0157] Experimental Example 5:

[0158] The only difference from Example 3 is that no titanium dioxide solution is added to the titanium dioxide modified solution.

[0159] Experimental Example 6:

[0160] The only difference from Example 3 is that titanium dioxide and sodium carboxymethyl cellulose are not added to the titanium dioxide solution.

[0161] The products of Experimental Examples 1-6 were tested for elasticity, anti-slip and breathability under normal conditions, and for stability under cold and hot weathering tests (the products were placed at -5°C for 24 hours, then at 70°C for 12 hours, and then irradiated with UV light for 6 hours at 500 kwh / m 2 ), the performance test results are shown in Table 2.

[0162] Table 2 Product performance test results of Experimental Examples 1-6:

[0163]

[0164] It can be seen from Experimental Examples 1-6 that when no modifier or titanium dioxide solution was added to the titanium dioxide modified liquid, the performance of the product showed a relatively obvious trend of deterioration. At the same time, when no dry nano-silicon dioxide, no boron nitride, no lanthanum chloride solution was added in the preparation of the added modifier, and no titanium dioxide and sodium carboxymethyl cellulose were added to the titanium dioxide solution, the performance of the product showed a trend of deterioration. The titanium dioxide modified liquid obtained by the specific method of the present invention using the added modifier combined with the titanium dioxide solution has the most obvious product performance effect, and other methods are not as significant as the effect of the present invention.

[0165] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0166] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a TPA high elastic material composition, characterized in that: The following steps are involved: Step 1: weigh the raw materials according to weight: 35-45 parts of TPE elastomer, 10-15 parts of EPDM, 8-12 parts of EVA, 7-11 parts of modified nano-attapulgite, 6-9 parts of anti-adjustment agent, 4-6 parts of zinc stearate, 1-2 parts of dicumyl peroxide, 2-4 parts of foaming agent, 2-3 parts of antioxidant and 1-2 parts of stearic acid; The preparation method of the modified nano attapulgite is: S01: Add 3-5 parts of nano-carbon powder and 2-4 parts of cerium nitrate solution to 5-8 parts of 4% dopamine hydrochloride solution by weight, then add 1-3 parts of silane coupling agent KH550, stir evenly, and obtain nano-carbon liquid; S02: pre-treating the nano-attapulgite by stirring in a sufficient amount of hydrogen peroxide solution, then washing with boiling water for 3 times, filtering and drying to obtain the pre-treated nano-attapulgite; The pretreated nano-attapulgite is placed in a nano-carbon solution 3-5 times the total weight of the pretreated nano-attapulgite for ultrasonic treatment, with an ultrasonic power of 350-400W for 30 minutes, filtered and dried to obtain a nano-carbon-polyphonic nano-attapulgite agent; S03: mixing the nano-carbon composite nano-attapulgite agent and the titanium dioxide modified liquid in a weight ratio of 5:3, and subjecting the mixture to ball milling. After the ball milling is completed, the mixture is filtered and dried to obtain a modified nano-attapulgite. The preparation method of the titanium dioxide modified liquid is: S031: 2-5 parts of titanium dioxide, 1-2 parts of sodium carboxymethyl cellulose and 5-8 parts of 5% chitosan solution are uniformly mixed by weight to obtain titanium dioxide solution; S032: First, the nano-silicon dioxide is stirred thoroughly in a 5% by mass sulfuric acid solution, and then washed with water, filtered, and dried to obtain dry nano-silicon dioxide; the dry nano-silicon dioxide, boron nitride and a 3-5% by mass lanthanum chloride solution are mixed and ball-milled in a weight ratio of (3-5):2:(5-7), the ball milling speed is 1000r / min, the ball milling is carried out for 2h, and after the ball milling is completed, the mixture is filtered, dried, and the added modifier is obtained; S033: adding the additive modifier to the titanium dioxide solution which is 3-5 times the total weight of the additive modifier, and stirring the solution until the stirring is completed, thereby obtaining a titanium dioxide modified solution; The preparation method of the resistant agent is as follows: S101: silane coupling agent KH560, ethanol and water are mixed in a weight ratio of 3:5:1 to obtain a silane coupling liquid; then barium carbonate is added to a sufficient amount of the silane coupling liquid and stirred to obtain a barium carbonate liquid; S102: 5-8 parts of barium carbonate solution, 1-2 parts of nano-silica sol, 3-4 parts of sodium silicate solution and 2-3 parts of magnesium oxide are mixed and ball-milled by weight at a ball-milling speed of 1500 r / min for 1 hour. After the ball-milling is completed, the mixture is filtered and dried to obtain a resistant agent; Step 2: The modified nano-attapulgite, the adjustment resistance, zinc stearate, and stearic acid are uniformly blended, and then sent into a mixer together with TPE elastomer, EPDM, EVA, dicumyl peroxide, a foaming agent, and an antioxidant for mixing at a mixing temperature of 120° C., a mixing time of 5 min, and a mixing speed of 100 r / min to obtain a mixing product; Step 3: The mixed product is sent to an open mixer for mixing for 10 minutes, and then pressed into a 3 mm thin sheet. Finally, the thin sheet is placed in a flat vulcanizer for mold foaming treatment. After the foaming is completed, a TPA high elastic material composition is obtained.

2. The method for preparing a TPA high elastic material composition according to claim 1, characterized in that: The compression foaming process uses a pressure of 10 MPa and a temperature of 175° C. for 300 seconds.

3. The method for preparing a TPA high elastic material composition according to claim 1, characterized in that: The foaming agent is foaming agent AC; the antioxidant is antioxidant MB.

4. The method for preparing a TPA high elastic material composition according to claim 1, characterized in that: The mass fraction of the hydrogen peroxide solution is 2-5%; the mass fraction of the cerium nitrate solution is 3-6%.

5. The method for preparing a TPA high elastic material composition according to claim 1, characterized in that: In S02, the stirring speed of the stirring pretreatment is 150-200 r / min, and the stirring is for 1 hour.

6. The method for preparing a TPA high elastic material composition according to claim 1, characterized in that: In S03, the mixing and ball milling treatment is performed at a ball milling speed of 1000-1500 r / min, and the ball milling is performed for 2 hours.

7. The method for preparing a TPA high elastic material composition according to claim 1, characterized in that: In S033, the stirring temperature of the stirring treatment is 60-65°C, the stirring speed is 550-750r / min, and the stirring is performed for 20 minutes.

8. The method for preparing a TPA high elastic material composition according to claim 1, characterized in that: The mass fraction of the sodium silicate solution is 2-5%.

9. A TPA high elastic material composition prepared by the preparation method of a TPA high elastic material composition according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Radiation-proof graphene natural rubber composite foam material and preparation method thereof

    CN116462889A

  • High-fidelity imitation metal light sensation rock plate and preparation method thereof

    CN117024115A